2017
DOI: 10.1007/s00294-017-0758-8
|View full text |Cite
|
Sign up to set email alerts
|

The m6A methyltransferase Ime4 and mitochondrial functions in yeast

Abstract: In eukaryotes, the precise transcriptional and post-transcriptional regulations of gene expression are crucial for the developmental processes. More than 100 types of post-transcriptional RNA modifications have been identified in eukaryotes. The deposition of N-methyladenosine (mA) into mRNA is among the most common post-transcriptional RNA modifications known in eukaryotes. It has been reported that mA RNA modification can regulate gene expression. The role of yeast mA methyltransferase (Ime4) in meiosis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…They showed that Ime4, yeast m6A methyltransferase, epi‐transcriptionally regulates triacylglycerol metabolism through the long‐chain fatty acyl‐CoA synthetase 71 . Another study also carried out by Yadav et al 72 . found that IME4 gene loss caused mitochondrial malfunction.…”
Section: Role Of M6a Modification In Lipid Metabolismmentioning
confidence: 97%
“…They showed that Ime4, yeast m6A methyltransferase, epi‐transcriptionally regulates triacylglycerol metabolism through the long‐chain fatty acyl‐CoA synthetase 71 . Another study also carried out by Yadav et al 72 . found that IME4 gene loss caused mitochondrial malfunction.…”
Section: Role Of M6a Modification In Lipid Metabolismmentioning
confidence: 97%
“…The genome-wide distribution of n6-methyladenosine (m6A) was unclear until 2012, but m6A is the most common RNA modification of mRNAs. It is enriched in many eukaryotic species of mammals, plants, and yeast [1][2][3][4][5][6][7][8] and is found in prokaryotes, including bacteria and mycoplasma [9,10]. The mRNAs of 7676 mammalian genes were found to be modified by m6A [11].…”
Section: Introductionmentioning
confidence: 99%
“…2a). In addition to its direct effect on regulating triacylglycerol (TAG) metabolism in haploid cells, IME4 deletion caused mitochondrial fragmentation and dysfunction, which indirectly influenced TAG metabolism [65] (Fig. 2a).…”
Section: Metabolismmentioning
confidence: 99%